2017
DOI: 10.1016/j.rmed.2016.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of urinary desmosines as a noninvasive diagnostic biomarker in patients with idiopathic pleuroparenchymal fibroelastosis (PPFE)

Abstract: Urinary desmosines may be a useful diagnostic biomarker in patients with PPFE. Measurement of desmosines combined with specific clinical and radiological features of PPFE may lead to an accurate diagnosis without SLB in patients with PPFE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Histologically, the interstitial increase in predominantly elastic fibers is the fundamental pathogenesis of PPFE [10,11]. Oyama et al [23] reported that urinary concentrations of desmosine were significantly higher in PPFE patients than in IPF patients. In the present study, we showed that the serum concentration of LTBP-4 in IPPFE patients was significantly higher than that in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, the interstitial increase in predominantly elastic fibers is the fundamental pathogenesis of PPFE [10,11]. Oyama et al [23] reported that urinary concentrations of desmosine were significantly higher in PPFE patients than in IPF patients. In the present study, we showed that the serum concentration of LTBP-4 in IPPFE patients was significantly higher than that in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum autoantibodies and rheumatologic markers like rheumatoid factor and myeloperoxidaseantineutrophil cytoplasmic antibody revealed undetermined significance [3,[25][26][27][28]. Increased levels of urinary desmosine have been shown by Oyama et al in a preliminary study including individuals with biopsyproven PPFE compared to idiopathic pulmonary fibrosis, chronic obstructive pulmonary disease and healthy control subjects with a potential utility of this test as a noninvasive diagnostic marker in patients with suspected but unbiopsied cases of PPFE [29]. None of these indicators are in routine clinical use due to their undetermined significance for PPFE.…”
Section: Discussionmentioning
confidence: 99%
“…patients with idiopathic pulmonary fibrosis, chronic obstructive pulmonary disease, and healthy control subjects revealing the potential utility of this test as a non-invasive diagnostic marker in suspected PPFE cases (26). KL-6 and SP-D may be elevated inconsistently in PPFE with unclear consequence while high levels of rheumatologic markers may exist without any significance (6,27,28).…”
Section: Oyama Et Al Have Shown Increased Levels Of Urinary Desmosine...mentioning
confidence: 98%